BS EN IEC 61557-14. Electrical safety in low voltage distribution systems up to 1 000 V a.c and 1 500 V d.c. Equipment for testing, measuring or monitoring of protective measures. Part 14. Equipment for testing the safety of electrical equipment for machinery (30th April 2021) - British Standards Institution,
No abstract available